Induced pluripotent stem cell line derived from a sporadic amyotrophic lateral sclerosis patient - Baofeng Feng; Jun Ma; Asiamah Ernest Amponsah; Ruiyun Guo; Desheng Kong; Jingjing He; Yawen Jiang; Wei Zhang; Zhanchi Zhang; Yongzhou Song; Sanbing Shen; Timothy O'Brien; et al. (Stem Cell Research, 2020)
Induced pluripotent stem cells (iPSCs) were generated from peripheral blood mononuclear cells (PBMCs) obtained from a 60-year-old female diagnosed with sporadic amyotrophic lateral sclerosis (sALS). The iPSCs shared the same karyotype with the parent PBMCs, expressed pluripotency stem cell markers, and demonstrated trilineage differentiation potential. This cell line could serve as an ideal model to investigate the mechanisms underlying amyotrophic lateral sclerosis (ALS).